(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
There has been growing awareness about quality in blood transfusion services with the objective of releasing only those blood products and blood which fulfill the desired standards in terms of safety and efficacy. Consistency is the hallmark of quality and can be achieved only through the use of standard operating procedures (SOP) by all staff engaged in blood centres at all times. Use of SOPs has also become essential for licensing and accreditation. Each blood bank has to develop its own set of SOPs matching their requirement and resources. SOP need to be developed for all critical procedures. There is now an international unanimity on the framework of SOPs. Each SOP must have the following components Each SOP must be given a unique identity number along with the revision number, if any. Information about the procedure, location where the SOPs will be used, its function and distribution list date from which it will be effective and signatures of the author(s) and the person from top management who can authorize the use of SOP from the effective date must precede the technical details.